A Legal Analysis on the Crime of Insulting the President and/or Vice President in the Criminal Code Based on the Principle of Freedom of Expression - Wildana, Afnan; Muazzin Muazzin; Rizanizarli Rizanizarli (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Articles 218–220 of Law Number 1 of 2023 concerning the Criminal Code regulate the offense of insulting the President and/or Vice President. These provisions constitute complaint-based offenses, meaning prosecution can only proceed upon a complaint filed by the President or Vice President as the direct victim. Nevertheless, the regulation raises various legal issues concerning criminalization policy, human rights protection, and its practical implementation in law enforcement. This study aims to analyze the regulation of insults against the President and/or Vice President from the perspective of criminal law principles and the guarantee of freedom of expression. The research employs a normative juridical method using statutory, conceptual, and case approaches. Data were obtained from secondary legal materials, including primary and secondary sources, and analyzed qualitatively. The findings indicate that the provisions serve as a form of social control intended to protect state interests, particularly the dignity and honor of the state, as represented by the President and/or Vice President. The regulation is not designed to create discrimination against the principle of equality before the law. Its application is limited by Article 218 paragraph (2), which excludes certain expressions from criminal liability, and Article 220, which establishes the offense as complaint-based. Therefore, protecting the honor of state officials must remain balanced with safeguarding citizens’ freedom of expression.